"Forever Gordon": Portrait of a Master Scholar with a Global Perspective - Lubetski, Meir (The Biblical archaeologist, 1996)
A rare combination of scholarly gentleman, mentor, and teacher par excellence, Cyrus Gordon's life overflows with unique experiences and soaring achievements. Often blazing trails on the edge of scholarship, it is gratifying to behold the esteem in which growing circles hold this "scholar for all seasons."